Innovation in Education : Preliminary Analysis for Inquiry-Based Biology Magazines - Erfina Erfina; Nurul Fauziah; Nurkhoiro Hidayati (PAIDAGOGIA: Jurnal Inovasi Pendidikan dan Pembelajaran, 2024)
This research aims to describe the results of the preliminary research phase as a basis for developing inquiry-based biology magazines for eleventh-grade students at SMA 11 Pekanbaru. This type of research is a development study utilizing the Plomp development model, which consists of three stages; however, this study only reaches the first stage, the preliminary research phase. The sample size for this research is 38 eleventh-grade students from SMA 11 Pekanbaru. The research instruments include observation sheets, interview sheets, and student needs questionnaires. Most students, 92.11%, prefer to learn using image examples, indicating a preference for visual media, and 97.37% are enthusiastic about developing inquiry-based biology magazines. Based on the preliminary research phase results, it can be concluded that the students need inquiry-based biology magazines.